Sistem Face Recognition Berbasis Web menggunakan OpenCV Serta Evaluasi dengan Metode System Usability Scale - Vanessa Shinta Putri; Gentur Wahyu Nyipto Wibowo; Ahmad Khanif Zen (TIN: Terapan Informatika Nusantara, 2026)
The attendance system is one of the important aspects for Tabebuya Resort and Restaurant for systematic human resource processing, the attendance system needed to be the basis for calculating salaries, evaluating discipline, and assessing the work of each employee. Therefore, an accurate, efficient, and transparent abscess system is needed so that the company’s productivity can be properly maintained. This research aims to develop the attendance system used by Tabebuya into a web-based face recognition system to make it easier for every employee to access the attendance system used by Tabebuya which originally had a problem in attendance recapitulation which had an effect on salary dan the failure of finger detection which had an effect in operational speed and long queues to become a web-based face recognition atttandance system to make it easier for every employee to access the attendance system with their own device with a certain coordinate point for avoiding operational disruptions and providing roleaccess limits to avoid manipulation of data. In the development of the system the programming, the software development method uses the waterfall method with the python program language implementation by OpenCV library to process facial features using biometric identification to recognize individuals based on facial characteristics and becomes an additional value to avoid the problem of attendance manipulation. The system evaluation is carried out using the system usability scale (SUS) method to ensure that the system created is technically functional. With >80,3 score of SUS indicate the web-based face detection attendance system developed using OpenCv is successful in usability and can help improvement of human resource management in company.